INOVASI MODUL EMBEDDED-IOT SEBAGAI MEDIA PEMBELAJARAN STEM DI SMK: STUDI KASUS DI SMK SIANG DAN SMK KAWUNG 1 SURABAYA - Tamaji, Tamaji; Dhaniswara, Erwin; Paramitha, Melvie (Lembaga Penelitian Dan Pengabdian Kepada Masyarakat Universitas 17 Agustus 1945 Surabaya, 2025)
The application of Embedded-IoT technology in STEM education at vocational schools is an innovation that aims to improve the quality of learning and students' readiness to face modern technological developments. This service was carried out at SMK Siang and SMK Kawung 1 Surabaya, which have limited infrastructure and human resources in utilizing IoT technology. Through the development of the Embedded-IoT module, this activity provides interactive and practical training to teachers and students to increase their understanding of IoT technology. This project involves creating 10 Embedded-IoT practicum modules and preparing STEM-based learning materials. It is hoped that the implementation of this module can improve the technology skills of students and teachers, strengthen the STEM-based curriculum, and increase the competitiveness of graduates in the job market. Apart from that, this activity also contributes to the implementation of the Independent Campus Learning Program (MBKM) and Key Performance Indicators (IKU) which encourage collaboration, active participation and strengthening technological capabilities in Vocational Schools. The embedded-IoT module implementation program at SMK SIANG and SMK Kawung 1 Surabaya aims to increase student and teacher competency in IoT technology through training, curriculum development and module implementation. The evaluation showed an increase in the average score from 62.8 (pre-test) to 72.2 (post-test), confirming the increase in participants' understanding and skills. A total of 10 modules are designed for STEM-based learning, providing practical experience in developing embedded systems and IoT. The results of this program have succeeded in improving the quality of education, supporting the integration of IoT technology in the teaching and learning process, and strengthening students' readiness to face modern industry.